Transformation of Islamic Law in Responding to the Challenges of Plurality in the Digital Era - Rini Rahmadani; Kurniati Kurniati; Qadir Gassing (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
This study examines the transformation of Islamic law in addressing the challenges of religious and ideological plurality in the digital era. Drawing on a qualitative, descriptive-analytical approach, the research explores how Islamic legal norms adapt to the complexities of online religious discourse, the decentralization of authority, and the rise of interpretive subjectivities. Using the framework of maqÄá¹£id al-sharÄ«â€˜ah, wasatiyyah (moderation), and Islamic multiculturalism, the study highlights the dynamic role of Islamic law as both a normative system and a socio-ethical mechanism. Findings indicate that Islamic law, when recontextualized through digital realities and pluralistic values, remains responsive to contemporary issues such as freedom of expression, extremism, and identity diversity. However, the fluidity of online interpretations and the erosion of traditional legal authority pose challenges to legal stability and epistemological coherence. The study concludes that a renewed interdisciplinary approach - integrating Islamic legal theory, digital sociology, and pluralism studies - is essential to ensure the continued relevance of Islamic law in shaping justice and coexistence in a globally connected society.